Digital gangrene associated with anticentromere antibodies - Mary Grace; Varada; E S Dhanesh (Wolters Kluwer Medknow Publications, 2014)
Anticentromere antibodies have been associated with peripheral vascular occlusive disease, but then it is mostly accompanied by sclerodactyly in the context of a connective tissue disorder. We report a case of digital gangrene in a 75 year old lady with no other associations except positive anticentromere antibodies.